Sublingual Hematoma Linked to Uncontrolled Warfarin Use: A Case Report - Kara, Hasan; Bayır, Aysegul; Ak, Ahmet; Degırmencı, Selim; Acar, Demet; Istanbulluoglu, Rabia (Fırat University, 2012)
Anticoagulant treatment is a vital treatment method used in prophylaxis and treatment of tromboembolic diseases. In anticoagulant treatment, the most significant complication that can sometimes threaten patient's life is hemorrhage. Therefore, planning anticoagulant treatment in a way not to cause thrombosis or bleeding and meticulous clinical and laboratory follow-up is vital. Hemorrhage in sublingual area is very rare. However, warfarin related bleeding in this area is life threatening and it might require securing patient's airway. In its treatment, it is recommended that anticoagulation with vitamin K, pro-thrombin complex concentrate (PCC) and fresh frozen plasma (FFP) be reversed immediately. In this article, a case who developed sublingual hemorrhage caused by prophylactic warfarin intake due to Coronary Artery Bypass Graft (CABG) has been presented.

Antikoagülan tedavi, tromboembolik hastalıkların profilaksi ve tedavisinde yaşamsal önem taşıyan bir tedavi yöntemidir. Antikoagülan tedavinin hasta hayatını tehdit edebilen en önemli komplikasyonu kanamadır. Bu nedenle antikoagülan tedavinin tromboz veya kanamaya yol açmayacak şekilde planlanması, klinik ve laboratuvar takibinin titizlikle yapılması yaşamsal önem taşımaktadır. Sublingual bölgeye kanama çok nadir görülmektedir. Ancak warfarine bağlı bu bölgedeki kanamalar hayatı tehdit edici bir durumdur ve hastanın havayolunun güvence altına alınması gerekebilir. Tedavide K vitamini, protrombin kompleks konsantresi ve taze donmuş plazma ile antikoagülasyonun biran önce tersine çevrilmesi önerilmektedir. Bu makalede Coronary Artery Bypass Graft nedeniyle profilaktik olarak warfarin alımına bağlı sublingual hematom gelişen bir olgu sunulmuştur.
Kontrolsüz Warfarin Kullanımına Bağlı Gelişen Sublingual Kanama: Olgu Sunumu